2013
DOI: 10.1111/ijfs.12454
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of extraction and isolation efficiency of catechins and caffeine from green tea leaves using different solvent systems

Abstract: Summary Catechins from green tea (Camellia sinensis L.) have received considerable attention due to their beneficial effects on human health, such as antioxidant and anticancer activities. Optimisation of extraction conditions of the catechins from green tea leaves was performed using different solvents (ethanol or distilled water), different extraction methods (ultrasound‐assisted, room temperature or reflux extractions) and various extraction times (0.5–24 h). The optimal extraction conditions were determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 29 publications
1
28
0
2
Order By: Relevance
“…Solvent type has been demonstrated to play a vital role in the extraction efficiency and ingredient proportion of the extracts from green tea (Perva‐Uzunalić and others ; Hu and others ). The obtained results are supported by previous studies that have shown that ethyl acetate can efficiently extract catechins from tea infusion (Choung and others ; Hu and others ), and anthocyanins are soluble in polar solvents (Kong and others ; Morais and others ). According to the results presented in Table , catechins accounted for about 72.72 and 66.38% of total phenolics in ZWE and ZEE, respectively, suggesting that they are the main phenolic compounds in both extracts.…”
Section: Resultssupporting
confidence: 88%
“…Solvent type has been demonstrated to play a vital role in the extraction efficiency and ingredient proportion of the extracts from green tea (Perva‐Uzunalić and others ; Hu and others ). The obtained results are supported by previous studies that have shown that ethyl acetate can efficiently extract catechins from tea infusion (Choung and others ; Hu and others ), and anthocyanins are soluble in polar solvents (Kong and others ; Morais and others ). According to the results presented in Table , catechins accounted for about 72.72 and 66.38% of total phenolics in ZWE and ZEE, respectively, suggesting that they are the main phenolic compounds in both extracts.…”
Section: Resultssupporting
confidence: 88%
“…7 Among them, EGCG is the most abundant one as it constitutes ~50% of total catechins in dried green tea leaves. 8 As tea leaf waste is also a rich source of catechins, 9 it would be a great advantage to the tea beverage industry to isolate catechins from tea leaf waste for further commercial production and utilization as a nutritional supplement or as an anticancer agent. Due to high-polarity nature of catechins, catechins in tea leaves are often extracted with polar solvents such as methanol, ethanol, acetonitrile, and acetone alone or in combination.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, tea components especially catechins, theanine and caffeine might be regarded as candidate inhibitors of these diseases. However, much more animal experiments should be carried out to confirm the obtained results; in particular, dose and style of drinking tea should be carefully formulated for the special prevention purpose; much more studies should be carried out to illustrate the inhibitory mechanisms of the tea components on the enzymes, and some novel techniques with high yield or purity of the tea components might also be developed furthermore although many approaches had been attempted (Chandini et al, 2011;Zhang et al, 2012;Choung et al, 2014). Nevertheless, tea is a well-known healthy beverage, and why do not we stop for tea?…”
Section: Discussionmentioning
confidence: 99%